MODERN PRODUCTS FOR FEEDING PREMATURE BABIES - A. V. Surzhik (Педиатрическая фармакология, 2012)
In recent decades there has been substantial progress in the technology of premature infants nursing, especially with extremely low birth weight. Adequate feeding is one of the fundamental factors of premature babies nursing. To ensure a premature baby with all necessary components for power saving in breast milk intake, breast milk fortifiers — specifically developed additives that adjust the composition of food for premature babies, are used for more than 20 years (for premature babies receiving breast milk). On the one hand, to preserve all benefits of breastfeeding, on the other — to prevent the deficit development of necessary elements for adequate growth and development of nutrients.